Pathogenic relations between metabolic and gynecologic disorders in acromegaly: a clinical case report - Alexander S. Lutsenko; Svetlana Yu. Vorotnikova; Irina V. Stanoevich; Tatiana S. Zenkova; Vilen N. Azizyan; Andrey Yu. Grigoriev; Zhanna E. Belaya (Ожирение и метаболизм, 2017)
Acromegaly is a neuroendocrine disorder with multiple comorbidities. In this article, we present a patient with long-term active acromegaly, without clinical remission after repeated neurosurgery and long-term treatment with somatostatin analogue. After the first neurosurgical treatment, cyclic ovarian function improved. Taken together with progressing metabolic disorders, it led to clinical manifestation of adenomyosis, which presented by algomenorrhea, menometrorrhagia and severe anemia. Due to clinical manifestation and extent of the disease, the patient underwent hysterectomy. Histologically we observed adenomyosis II with 2/3 myometrialpenetration. This clinical case highlights the importance of gynecological assessment among patients with acromegaly of late reproductive and premenopausal period.